Stem cells for the treatment of glioblastoma: a 20-year perspective - Anda-Alexandra Calinescu; McKenzie C Kauss; Zain Sultan; Wajd N Al-Holou; Sue K O’Shea (CNS Oncology)
Glioblastoma, the deadliest form of primary brain tumor, remains a disease without cure. Treatment resistance is in large part attributed to limitations in the delivery and distribution of therapeutic agents. Over the last 20 years, numerous preclinical studies have demonstrated the feasibility and efficacy of stem cells as antiglioma agents, leading to the development of trials to test these therapies in the clinic. In this review we present and analyze these studies, discuss mechanisms underlying their beneficial effect and highlight experimental progress, limitations and the emergence of promising new therapeutic avenues. We hope to increase awareness of the advantages brought by stem cells for the treatment of glioblastoma and inspire further studies that will lead to accelerated implementation of effective therapies.